Obstructive sleep apnea syndrome should be considered as a cause of nocturia in younger patients without other voiding symptoms - Maeda, Takahiro; Fukunaga, Koichi; Nagata, Hirohiko; Haraguchi, Mizuha; Kikuchi, Eiji; Miyajima, Akira; Yamasawa, Wakako; Shirahama, Ryutaro; Narita, Midori; Betsuyaku, Tomoko; Asano, Koichiro; Oya, Mototsugu (Canadian Urological Association Journal, 2016)
Introduction: This study aimed to evaluate urination frequency among patients with obstructive sleep apnea syndrome (OSAS) and the effect of continuous positive airway pressure (CPAP) treatment. Methods: We evaluated 138 men with moderate-to-severe OSAS by using polysomnography. Urination status was assessed at baseline and three months using the International Prostate Symptom Score and Overactive Bladder Symptom Score. Nocturia was defined as ≥2 nighttime urinations and patients were classified into Group A (<50 years old with nocturia), Group B (≥50 years old with nocturia), and Group C (patients without nocturia). OSAS severity and other urinary symptoms were also evaluated. Results: Patients with nocturia exhibited more severe OSAS, compared to patients without nocturia (apnea-hypopnea index [AHI]: 52.0 vs. 44.7; p=0.021). Group A had the worst AHI, but did not have additional voiding symptoms, compared to Group B (p<0.001). The number of urinations was significantly correlated with OSAS severity in <50-year-old patients (p=0.013). CPAP reduced the number of urinations in Group A (75% of patients) and Group B (90% of patients). Patients with and without improved nocturia exhibited significant differences in their baseline OSAS severity (AHI: 53.7 vs. 37.3; p=0.042). Conclusions: OSAS severity was associated with the number of urinations in <50-year-old patients. CPAP decreased the nocturia frequency in 85% of patients with nocturia and was most effective in patients with severe AHI. However, additional studies should evaluate voiding volume in order to elucidate the mechanism of nocturia in patients with OSAS.